Graft orientation influences meshing ratio - Capek, Lukas; Flynn, Cormac; Molitor, Martin; Chong, Simon; Henys, Petr (Burns, 2018)
OBJECTIVES: The technique of meshed skin grafting is known since 1960s. It was shown that there is a difference between the declared and real expansion ratio of the skin meshed graft. We hypothesize that the orientation of the Langer's lines in a split thickness skin graft is a key parameter in the resulting expansion ratio. METHODS: The skin graft meshing process was analyzed in two steps. In the first step, ex vivo uniaxial tests of human skin were performed. This served as an input for the constitutive model used for numerical simulations. In the second step, finite element analyses were performed so that stress distributions and expansion ratios could be determined. RESULTS: It was shown that peaks of true stress tended to be concentrated around the vertex of the mesh pattern region for all cases. The declared expansion was impossible to obtain for all expansion ratios having the meshing incision perpendicular to the Langer's lines. The highest difference between declared and real expansion ratio reaches 37%. CONCLUSIONS: With regard to literature dealing with expansion of skin grafts by meshing, a high scatter amongst data results is observed. This finding was also explained by our research, demonstrating the significance of Langer's lines and their relative orientation to the direction of meshing.
Keywords: Dermatologic Surgical Procedures; fyziologie kůže; Skin Transplantation; Biomechanics; transplantáty; transplantace kůže; Langer line; Finite Element Analysis; lidé; Finite element method; Tensile Strength; kůže; mechanický stres; Stress, Mechanical; biomechanika; Skin; expanze tkáně; Transplants; Skin Physiological Phenomena; analýza metodou konečných prvků; Tissue Expansion; dermatochirurgické výkony; Burn; Biomechanical Phenomena; pevnost v tahu; Humans